The effect of Covid-19 pandemic on healthy lifestyle behaviors and quality of life in Turkey - Diedhiou, Azize Bingöl; Yilmaz, Fikriye; Yılmaz, Atakan (University School of Physical Education, 2021)
Introduction. It is very important to understand the potential for change in healthy lifestyle behaviors and quality of life of individuals before and during the COVID-19 pandemic. Aim of Study. The aim of this study was to examine changes in healthy lifestyle behaviors and quality of life in individuals living in Turkey before and during the COVID-19 pandemic from March to May 2020. Material and Methods. A total of 921 individuals were selected by convenience and snowball sampling in Turkey. The data of the study were collected using an online questionnaire. The questionnaire consisted of four parts, the first part comprised questions determining socio-demographic characteristics, the second part was the International Physical Activity Questionnaire (IPAQ) to determine the level of physical activity, the third part was a self-administered questionnaire which was developed by Sakamaki et al. (2005) as an eating habits questionnaire [23], while the last part was the Visual Analog Scale to measure the quality of life of respondents. Results. The average age of the participants was 29.38 ± 9.16 years, 57.2% were women, 61.6% worked and 53% fell in the professional jobs category. It was found that the participants’ body mass index (BMI) increased 50.3% during the curfew period in the beginning of the COVID-19 pandemic (p < 0.05). According to IPAQ results, physical activity levels of the participants decreased statistically during the pandemic (p < 0.5). Considering the variables evaluating changes in participants’ dietary habits, there was a statistically significant increase in regular breakfast preparation and snack consumption during the day (p < 0.05). Almost half of the participants (46%) reported that their quality of life had deteriorated during the pandemic. Conclusions. Consequently, when trying to prevent the COVID-19 infection or any epidemic in the short term, it is recommended not to neglect its effects on the quality of life and healthy lifestyle behaviors of the general population in the long term. © 2021, University School of Physical Education. All rights reserved.
Keywords: COVID-19; Healthy behaviors; Nutrition; Physical activity; Quality of life